Investigation of fractal antenna on the base of the Sierpinski triangle to apply in wireless technologies - Temirbayev, А.А.; Imanbayeva, А.К.; Kapurnova, С.; Uralbayeva, D. (Recent Contributions to Physics, 2015)
Now a special attention is paid to multi-band and high-frequency antennas based on fractal structures. Antennas with fractal structure due to their geometrical shape compared to conventional antennas do have some advantages. Fractal Antenna based Sierpinski fractal and its modified form were designed. Fractal antennas have previously been modeled in the package Ansoft HFSS. The features of these antennas as compared with the whip antenna are determined. According to indicators such as speed and distance data fractal antenna showed its competitiveness.
Keywords: fractal antennas; Sierpinski triangle (fractal); radiation pattern; Wi-Fi